The Levels of Cholinesterase Enzyme and Hemoglobin in Linggasari Village’s Farmers - Siti Munfiah; Yudhi Wibowo; Octavia Permata Sari; Diah Krisnansari; Muhammad Zaenuri Syamsu Hidayat (Jurnal Kesehatan Masyarakat, 2023)
Farmers in Linggasari Village often mix pesticides, did not use pesticides that follow the dose, did not use PPE completely, eat, drink or smoke did not clean themselves after spraying. Some types of pesticides can reduce cholinesterase enzyme and hemoglobin levels. The study aimed to analyze the factors that correlated with cholinesterase enzyme and hemoglobin levels of spraying farmers. This was a cross-sectional study conducted from March to April 2022. The population of this study was all farmers who use pesticides, as many as 30 farmers qualify the inclusion criteria, namely male spraying farmers aged over 18 years, the maximum last contact time with pesticides was two months before the study was conducted. The independent variables were age, BMI, working period, frequency of spraying, duration of spraying, and PPE usage score. The dependent variables included cholinesterase and hemoglobin levels. Bivariate analysis was assessed with Pearson Correlation Test or Spearman Correlation Test, while multivariate analysis used linear regression. The results showed that age (p=0,032, r=0,391) and BMI (p=0,036, r= 0,385) correlated with cholinesterase enzyme, and age (p=0,000, r=0,615) correlated with farmers' hemoglobin levels. The results of multivariate analysis that the most influential factor on cholinesterase enzyme and hemoglobin levels was age.